Comparison of three obturation techniques with regard to bacterial leakage - Cleber Keiti Nabeshima; Guilherme Henrique Rosa Martins; Mário Francisco de Pasquali Leonardo; Regina Célia Furukava Shin; Silvana Cai; Manoel Eduardo de Lima Machado (Universidade Estadual de Campinas, 2015)
Aim: To compare bacterial leakage in root canals obturated with the modified single-cone, lateral condensation, and continuous wave of condensation techniques. Methods: Distobuccal root canals of maxillary molars were shaped up to ProTaper F2 and obturated with modified singlecone, lateral condensation or continuous wave of condensation technique. Two-chamber bacterial model using Enterococcus faecalis was employed for bacterial leakage evaluation for 30 days. The chi-square test was applied to evaluate differences between turbid and non-turbid samples, and the Kruskal-Wallis test was used for evaluating the time necessary for microleakage. A significance level of 5% was set for all analyses. Results: The modified single-cone technique showed leakage in 73.3% of samples, lateral condensation in 66.6%, and continuous wave of condensation in 53.3%, but there were no significant differences among the groups (p>0.05). Conclusions: It can be concluded that the modified single-cone technique shows similar sealing efficacy to that of lateral condensation and continuous wave of condensation technique.